Optimization of the water-based polyurethane with acrylate terminal process in nylon fabrics application using the Taguchi-based gray relational analysis method. Issue 11 (June 2021) - Kuo, Chung-Feng Jeffrey; Dong, Min-Yan; Yang, Chi-Ping
This study synthesized the water-permeable and hydrophobic property of water-based polyurethane (WPU) and applied it to nylon fiber-based functional textiles. Specifically, poly-stearyl acrylate (PSA) homopolymers with different molecular weights were used as end-capping agents in the WPU to form water-based polyurethane with acrylate terminal (WPUA). In the WPUA process, dimethylacetamide was adopted as a neutralizing agent to form a stable WPUA emulsion. The effects of the design parameters, such as the hydrophilic ionic group dimethylol propionic acid (DMPA), the PSA molecular weight and content, were set as the control factors and are analyzed by the Taguchi method and gray relational analysis (GRA). The water-repellent characteristic, water vapor permeability (WVP) and fabric flexural rigidity were considered as performance parameters as multi-qualities. The Taguchi method was based on the analysis of variance and implemented orthogonal arrays for experimental design. Each performance parameter was optimized independently. Then, the performance parameters were optimized together with GRA. According to the experimental results, the most important factor for the water-repellent characteristic, WVP and fabric flexural rigidity is the DMPA content, followed by the PSA molecular weight and content. The corresponding results showed that in the optimal parameter combination, the content of DMPA was 30.8 phm (parts per hundred monomer by weight), the PSA molecular weight was 3000 g/mol and the PSA content was 4 phm. After WPUA padding, the water contact angle of the water-repellent nylon was 135.3°, the WVP was 2271.7 g/m 2 /day and the flexural rigidity was 2.7 cm.